EXPLORING INDONESIAN TRANSLATED COLLOCATION IN J.K ROWLING’S NOVEL” HARRY POTTER AND THE PRISONER OF AZKABAN” - Fatich Narulita Mahendra Faradilla (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Translation is an effort to transfer messages from one language (source language) to another language (target language) or an attempt to re-express messages in one language (target language) in another language (source language). Students need to learn about translation, especially students at universities who take English education. Moreover, people who like reading novels, magazines, newspapers, comics, poetry, and listening to English songs will enjoy it if the translator can translate with the right sentence. This study aimed to find out how the English collocations in J.K Rowling’s Novel “Harry Potter and the Prisoner of Azkaban” are translated into the Indonesian version. The research method for this research was used qualitative analysis. There are 51 collocations found in chapter one until four of J.K Rowling’s Novel “Harry Potter and the Prisoner of Azkaban”, which consist of 36 group of words for Lexical Collocation and 15 group of words for Grammatical Collocation. Out of the seven-translation procedures, four are used in this research. As a result of the analysis, literal translation occurs as the translation procedure that is frequently used in translating English collocations. There are 39 Literal Translation procedure, 3 Transposition, 6 Equivalence, and 3 Modulation translation procedure. The data collection procedures were performed by reading, highlighting and identifying, collecting by listing, classifying, and checking the English collocations. In this research, the instrument is the researcher herself as the main instrument. As a human instrument, in this study the researcher acted to collect appropriate data. The researcher processed the classification data as shown in the table 4.1: Data Identification.